2016
DOI: 10.1088/0031-9155/61/2/813
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the influence of oxygen on the PRESAGE®dosimeter

Abstract: It is generally accepted that the PRESAGE(®) radiochromic dosimeter is not sensitive to oxygen, however, this claim has not been supported or verified experimentally. Therefore, the aim of this study was to experimentally determine the potential influence of oxygen on dose sensitivity of the PRESAGE(®) dosimeter and its reporting system. Batches of PRESAGE(®) and its radical initiator-leuco dye reporting system were prepared in aerobic and anaerobic conditions. The anaerobic batches were deoxygenated by bubbli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…PRESAGE ® dosimeters also demonstrate a temperature dependence during radiation and storage [ 177 ] and some temporal instability [ 178 ] making it difficult to use the dosimeter with absolute calibration. Some dependence of the dose sensitivity on oxygen content in PRESAGE ® was also found [ 179 ]. Despite these unfavorable properties, the relative dose distribution was found to be reproducible within a 2% dose difference for an allowable distance-to-agreement of 2 mm [ 178 ], and PRESAGE ® was applied in some clinical dosimetric validation studies including IMRT [ 180 , 181 ], VMAT [ 182 , 183 ] in the determination of output factors of gamma knife radiosurgery [ 184 ] and in brachytherapy [ 185 , 186 , 187 ].…”
Section: Radiochromic Gel Dosimetersmentioning
confidence: 94%
“…PRESAGE ® dosimeters also demonstrate a temperature dependence during radiation and storage [ 177 ] and some temporal instability [ 178 ] making it difficult to use the dosimeter with absolute calibration. Some dependence of the dose sensitivity on oxygen content in PRESAGE ® was also found [ 179 ]. Despite these unfavorable properties, the relative dose distribution was found to be reproducible within a 2% dose difference for an allowable distance-to-agreement of 2 mm [ 178 ], and PRESAGE ® was applied in some clinical dosimetric validation studies including IMRT [ 180 , 181 ], VMAT [ 182 , 183 ] in the determination of output factors of gamma knife radiosurgery [ 184 ] and in brachytherapy [ 185 , 186 , 187 ].…”
Section: Radiochromic Gel Dosimetersmentioning
confidence: 94%
“…The investigation of the oxygen influence on PRESAGE demonstrated that PRESAGE was capable of maintaining good linearity (R 2 > 0.99), with or without the presence of oxygen [ 73 , 104 ]. Although good linearity was obtained by PRESAGE with the presence of a catalyst (DBTDL), the catalyst reduced the linearity by 2% [ 75 ].…”
Section: Sensitivity and Linearity Of Presagementioning
confidence: 99%
“…PRESAGE (LMG) [100] 0 Gy-30 Gy 0.9946 PRESAGE (MeO-LMG) [100] 0 Gy-30 Gy 0.9963 PRESAGE (Cl-LMG) [100] 0 Gy-30 Gy 0.9985 PRESAGE (Br-LMG) [100] 0 Gy-30 Gy 0.9997 PRESAGE (Bi Neo) [91] 0 Gy-30 Gy 0.9999 PRESAGE (DBTDL) [91] 0 Gy-30 Gy 0.9999 PRESAGE (Zn OCT) [91] 0 Gy-30 Gy 0.9999 PRESAGE (Iodoform) [93] 0 Gy-30 Gy 0.9988 PRESAGE (Bromoform) [93] 0 Gy-30 Gy 0.9996 PRESAGE (Chloroform) [93] 0 Gy-30 Gy 0.9980 PRESAGE (Organometallic catalyst) [75] 0 Gy-20 Gy 0.9700 PRESAGE (MOD 1) [92] 0 Gy-50 Gy 0.9984 PRESAGE (MOD 2) [92] 0 Gy-50 Gy 0.9993 PRESAGE (MOD 3) [92] 0 Gy-50 Gy 0.9989 PRESAGE (deoxygenation) [104] 0 Gy-30 Gy 0.9981 PRESAGE (no deoxygenation) [104] 0 Gy-30 Gy 0.9972…”
Section: Materials Dose Range Correlation Coefficientmentioning
confidence: 99%
“…In contrast the para -substituent DTBs have demonstrated the most facile color fading [ 39 ]. A combination of singlet oxygen and light is thought to be the cause of bleaching of DTBs [ 54 ] even though for these dosimeters the effect is minimal [ 55 ].…”
Section: Reviewmentioning
confidence: 99%